How many missed abortions are caused by embryonic chromosomal abnormalities and what are their risk factors? - Li, Xin; Kang, Han; Yin, Huifeng; Liu, Tianjiao; Hou, Qiannan; Yu, Xiaolan; Guo, Yuanlin; Shen, Wei; Ge, Huisheng; Zeng, Xiaoyan; Lu, Kangmu; Xiong, Ying (Frontiers in Genetics, 2023)
Introduction: Though embryonic chromosome abnormalities have been reported to be the most common cause of missed abortions, previous studies have mainly focused on embryonic chromosome abnormalities of missed abortions, with very few studies reporting that of non-missed abortion. Without chromosome studies of normal abortion samples, it is impossible to determine the risk factors of embryo chromosome abnormalities and missed abortion. This study aimed to investigate the maternal and embryonic chromosome characteristics of missed and non-missed abortion, to clarify the questions that how many missed abortions are caused by embryonic chromosomal abnormalities and what are their risk factors. Material and methods: This study was conducted on 131 women with missed or non-missed abortion from the Longitudinal Missed Abortion Study (LoMAS). Logistic regression analysis was used to identify the association between maternal covariates and embryonic chromosomal abnormalities and missed abortions. Data on the characteristics of women with abortions were collected. Results: The embryonic chromosome abnormality rate was only 3.9% in non-missed abortion embryos, while it was 64.8% in missed-abortion embryos. Assisted reproductive technology and prior missed abortions increased the risk of embryonic chromosome abnormalities by 1.637 (95% CI: 1.573, 4.346. P = 0.010) and 3.111 (95% CI: 1.809, 7.439. (P < 0.001) times, respectively. In addition, as the age increased by 1 year, the risk of embryonic chromosome abnormality increased by 14.4% (OR: 1.144, 95% CI: 1.030, 1.272. P = 0.012). Moreover, advanced age may lead to different distributions of chromosomal abnormality types. Conclusions: Nearly two-thirds of missed abortions are caused by embryonic chromosomal abnormalities. Moreover, advanced age, assisted reproductive technology, and prior missed abortions increase the risk of embryonic chromosomal abnormalities.